Lagu Tradisional Gorontalo Tidi Lo Polopalo sebagai Upaya Pelestarian Budaya bagi Generasi Muda - Ohi, Rahmawati (Jurusan Pendidikan Bahasa & Sastra Indonesia, Universitas Negeri Gorontalo, 2025)
Traditional songs constitute an essential element of intangible cultural heritage, functioning as a medium for transmitting values, identity, and collective memory. However, globalization and the dominance of popular culture pose significant challenges to their sustainability among younger generations. This study examines the role of teaching the Gorontalo traditional song Tidi Lo Polopalo as a cultural preservation strategy in formal education. Employing a qualitative descriptive approach with a field study design, the research was conducted at SMP Negeri 3 Bone, Gorontalo Province, involving 32 eighth-grade students. Data were collected through observation, interviews, and documentation, and analyzed using data reduction, data display, and conclusion drawing techniques. The findings reveal that contextual and participatory instruction of Tidi Lo Polopalo enhances students’ cultural understanding, strengthens local identity, and fosters appreciation of regional heritage. The song is perceived not merely as musical content but as a representation of Gorontalo’s historical and social values. The study underscores the strategic role of integrating traditional songs into arts education to ensure the sustainability of local culture through formal schooling.